2017
DOI: 10.1369/0022155417722118
|View full text |Cite
|
Sign up to set email alerts
|

Euptox A Induces G1 Arrest and Autophagy via p38 MAPK- and PI3K/Akt/mTOR-Mediated Pathways in Mouse Splenocytes

Abstract: Euptox A (9-oxo-10, 11-dehydroageraphorone), the main toxin isolated from Eupatorium adenophorum, is known to induce immunotoxicity in animals. However, the precise mechanism underlying the effects of Euptox A on splenocytes is unclear. Here, we aimed to investigate the molecular mechanisms underlying the effect of Euptox A in mouse spleens after its intragastric administration and found that Euptox A exhibits proautophagic effects in splenocytes. Euptox A markedly arrested the splenocytes in the G0/G1 phase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Based on the toxicology literature, it would seem plausible these sesquiterpenes could be possible causative agents for the splenic immunomodulatory effects noted here. A study by Mo et al [ 17 ] stated that Euptox A induced G 1 arrest and autophagy among the splenocytes of mice who had ingested the toxin. Ouyang et al [ 16 ] specifically reported that both DAOA and OA caused alterations in the histopathology of the spleens of mice that had been exposed to these toxic compounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the toxicology literature, it would seem plausible these sesquiterpenes could be possible causative agents for the splenic immunomodulatory effects noted here. A study by Mo et al [ 17 ] stated that Euptox A induced G 1 arrest and autophagy among the splenocytes of mice who had ingested the toxin. Ouyang et al [ 16 ] specifically reported that both DAOA and OA caused alterations in the histopathology of the spleens of mice that had been exposed to these toxic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Among the effects reported are abnormal liver hematology, jaundice, hepatocyte necrosis, bile duct hyperplasia, liver oxidative stress, and inflammation [ 13 , 14 , 15 ]. Other studies have also reported toxicity in the spleen, with characteristics like abnormal spleen cell proliferation, increased apoptosis, and tissue oxidative stress damage [ 16 , 17 , 18 ]. However, A. adenophora also have ethno-pharmacological uses, such as anti-malaria, anti-inflammation, analgesic, and wound healing [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These toxins are mainly found in the leaves with a mass percentage of 0.63–1.99 % in dry leaves [ 28 ]. 9-Oxo-10, 11-dehydro-agerophorone (euptox A) exhibited hepatotoxicity in rodents [ 7 , 29 , 30 , 31 ] with a median lethal dose (LD50) of 1470 mg/kg body weight of mice, whereas 2-deoxo-2-(acetyloxy)-9-oxo-ageraphorone(DAOA) and 9-oxo-agerophorone (OA) also showed hepatotoxicity in mice with respective LD50 of 926 mg/kg BW and 1470 mg/kg BW [ 27 ]. DAOA and euptox A are also immunotoxic to mice, showing characteristics such as reduction in numbers and irregular arrangement of splenocytes and thymocytes [ 13 ].…”
Section: Major Toxins In a Adenophora And Their Toxic Naturementioning
confidence: 99%
“…A current study by Okyere et al [ 15 ] reported that ODA caused apoptosis and G0/G1 cell arrest of hepatocytes in mice. In addition, in mouse splenocytes, ODA induced G1 arrest and autophagy [ 16 ].…”
Section: Introductionmentioning
confidence: 99%